Let's solve the equation correctly step by step:
-
Start with the original equation: \[ 3x + 2x - 6 = 24 \]
-
Combine like terms on the left side: \[ 5x - 6 = 24 \]
-
Add 6 to both sides to isolate the term with \( x \): \[ 5x = 30 \]
-
Divide both sides by 5: \[ x = 6 \]
The mistake in the original solution occurred when combining terms. The incorrect step was:
- Wrong Step: The solver incorrectly subtracted \( 2x \) twice from the equation, resulting in \( x - 6 = 24 \).
The correct approach is to combine \( 3x \) and \( 2x \) first, which yields \( 5x - 6 = 24 \). After correcting this step, the solution leads to \( x = 6 \) rather than \( x = 30 \).